2021
DOI: 10.1038/s41598-021-93035-9
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline extract of the seaweed Ascophyllum nodosum stimulates arbuscular mycorrhizal fungi and their endomycorrhization of plant roots

Abstract: Ascophyllum nodosum extracts (ANE) are well-established plant biostimulants that improve stress tolerance and crop vigour, while also having been shown to stimulate soil microbes. The intersection of these two stimulatory activities, and how they combine to enhance plant health, however, remains poorly understood. In the present study, we aimed to evaluate: (1) the direct effect of ANE on the arbuscular mycorrhizal fungus Rhizophagus irregularis, and (2) whether ANE influences endomycorrhization in plants. ANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Alkaline extracts of Ascophyllum nodosum enhanced the development of the mycorrhizal fungus Rhizophagus irregularis in terms of spore germination, germ tube length, and hyphal branching. The application of the extracts improved the formation of mycorrhizal associations, increased root colonization, arbuscular maturity, and the size of greenhouse-grown Medicago truncatula plants [140]. An Ascophyllum nodosum extract significantly improved the root, shoot, and fruit biomass productivity parameters by positively influencing the rhizospheric bacterial and fungal communities that are associated with pepper and tomato plants [141].…”
Section: Plant Growth Stimulation (Biostimulators and Biofertilizers)...mentioning
confidence: 99%
“…Alkaline extracts of Ascophyllum nodosum enhanced the development of the mycorrhizal fungus Rhizophagus irregularis in terms of spore germination, germ tube length, and hyphal branching. The application of the extracts improved the formation of mycorrhizal associations, increased root colonization, arbuscular maturity, and the size of greenhouse-grown Medicago truncatula plants [140]. An Ascophyllum nodosum extract significantly improved the root, shoot, and fruit biomass productivity parameters by positively influencing the rhizospheric bacterial and fungal communities that are associated with pepper and tomato plants [141].…”
Section: Plant Growth Stimulation (Biostimulators and Biofertilizers)...mentioning
confidence: 99%
“…The study conducted by Kuwada et al (2006) found that the extracts from red (including Gricilaria verrucosa, Gelidium amansii, and Eucheuma cottonii) and green algae (Chlorella pyrenoidosa) extracted in 25% methyl alcohol solution increased hyphal growth from AMF Gigaspora margarita and Glomus caledonium spores in vitro culture. Hines et al (2021) reported the stimulation of spore germination of the AMF Rhizophagus irregularis by extracts of seaweed Ascophyllum nodosum, which contained bioactive compounds (such as alginate-derived oligosaccharides, phlorotannins, and mannitol) in the extract. Campos-López et al ( 2022) also found that combinations of flavonoids and strigolactone with or without roots stimulated spore germination and the elongation and branching of hyphae of AMF.…”
Section: Discussionmentioning
confidence: 99%
“…Several companies such as Acadian Agritech, Agri Gro Marketing Inc., MainStream Organics, etc. have developed commercial plant growth biostimulants using A. nodosum as seaweed [105][106][107]. Kappaphycus alvarezii and Sargassum vulgare, red and brown seaweeds respectively, have also been combined in a commercial biostimulant called Reabilit Algas®, developed by Nutimax Fertilizantes company.…”
Section: Macroalgae As Bio-resource For Biostimulants Productionmentioning
confidence: 99%